History, Hysteria, and Hype: Government Contracting with Faith-Based Social Service Agencies - Queen, Edward (Religions, 2017)
In light of the adoption of the Charitable Choice Provision of the Welfare Reform Bill and the creation of White House Offices on faith based initiatives this article examines the history of government contracting with faith-based organizations to deliver human and social services with a particular focus on how the U. S. Supreme Court has viewed the legal status of such contracts.